From Aggregate Production Planning to Aggregate Energy Industrial Consumption Plans - Michel Leseure (Energies)
The increasing use of renewable energy sources in national electricity networks is challenging because of intermittence, i.e., the fact that the availability of the fuel (e.g., solar irradiance, wind) is volatile. This is a new challenge for the energy sector that has led to much research about energy storage. In the manufacturing sector, dealing with the volatility of demand is not a new problem and is addressed by the application of aggregate production planning techniques. Solving an aggregate production planning problem is about finding the best trade-off because capacity and inventory utilization. This paper explores the application of this technique to energy management problems and explains how it can be used as a complementary solution to energy storage, showing how industrial entities can play an active role in greening the electricity sector, solely through a different planning of their inventory levels.